Design, synthesis and biological evaluation of some new 2-Pyrazoline derivatives as potential anticancer agents - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
A new series of N-(4-(1-Phenyl-5-aryl-4,5-dihydro-1H-pyrazol-3-yl)phenyl)-4-substitutedbenzamide derivatives were designed and synthesized from new chalcone derivatives. All newly synthesized compounds were determined by using IR, H-1-NMR, C-13-NMR spectroscopic methods, elemental analysis and evaluated for their in vitro antiproliferative activities on HeLa, MCF-7, MKN-45 cancer cell lines and NIH-3T3 cell line using MTT assay. Expression of Bax and Bcl-2 proteins was detected by Western-blot analysis and caspase-3 enzyme activity was measured. Notably, compounds 1f and 2f showed a significant cytotoxic effect in all three cancer cells and did not display cytotoxicity on NIH-3T3 normal cells. (IC50 = 26.66 +/- 2.73 mu M on HeLa, IC50 = 9.41 +/- 2.19 mu M on MCF-7, IC50 = 5.17 +/- 3.54 mu M on MKN-45 for 1f. IC50 = 17.96 +/- 3.34 mu M on HeLa, IC50 = 0.69 +/- 0.13 mu M on MCF-7, IC50 = 0.88 +/- 0.16 mu M on MKN-45 for 2f.) Moreover, 1f and 2f upregulated protein expression level of Bax and downregulated protein expression level of Bcl-2 in cells. Similarly, caspase-3 activity was increased in cells via 1f and 2f. It can be concluded that 1f and 2f activated apoptosis by inducing mitochondrial apoptotic proteins in HeLa, MCF-7, MKN-45. This could be potentially new anti-cancer derivatives and used to contribute to new therapeutic development.
Keywords: Pyrazoline; Anticancer; Caspase activity; Apoptosis; Chalcone; MTT assay; HeLa; PYRAZOLINE DERIVATIVES; ANTIMICROBIAL ACTIVITY; INDOLE MOIETY; BEARING